Effect of E-procurement on Performance of Construction projects of Counties in Lake Region Economic Bloc, Kenya. - KENNEDY WANDERA WALUBENGO (International Journal of Business, Economics, and Social Development, 2025)
E-procurement is the use of ICT capabilities to decrease the human contact in procurement operations. E-procurement enables users to find goods in electronic catalogs, generate orders, route them for approval, create and transmit orders to suppliers, and automate the invoicing and payment process. The study's major goal was to look at the impact of E-procurement on the performance of construction projects in Kenya's Lake Region Economic Bloc counties. The study used an explanatory research design. A stratified random sampling approach was employed to choose 342 respondents from a target group of 2,346 County officers. Primary data were gathered through interviews and questionnaires. Data was analyzed for inferential as well as descriptive statistics using SPSS version 26 and theme analysis, respectively. E-procurement was established to be a strong predictor of the success of building projects in the Lake Region Economic Bloc counties. Electronic procurement can account for up to 76.2% of the variation in construction project performance (R2=0.762, P